Case of using mycophenolate in combination with steroids for concurrent macrophage activation syndrome and lupus flare. Issue 4 (7th April 2020) - Shah, Kavina; Porter, Andrew; Takhar, Gagandeep; Reddy, Venkat
Abstract : This report highlights the importance of tailored treatment strategies in severe systemic lupus erythematosus (SLE) flares driving the life-threatening condition, macrophage activation syndrome (MAS). We report the case of a 42-year-old woman with active systemic lupus erythematosus (SLE) who was diagnosed with MAS within 3 days of onset of lethargy, rash, joint pain and significant cytopenias. This early diagnosis meant that her condition was managed with less intensive immunosuppression with only modest doses of steroids and mycophenolate mofetil.